ANALISIS DAMPAK SOSIAL EKONOMI KEBIJAKAN PEMERINTAH (STUDI KASUS PPKM LEVEL 4 COVID-19 JAWA-BALI 2021) - Asep Rully Ferdiansyah (Badan Penerbit STIEPARI Press, 2022)
The pandemic COVID-19 is the health disaster that becomes the threat for many countries including Indonesia. Since the first positive case of COVID-19 found in March 2020 in Indonesia, the government has made policies starting from the Great Social Restriction (GSR), then changed into the Enforcement of Emergency Community Activity Restriction (ECAR), and finally became the Enforcement of Community Acvitity Restriction (ECAR) Level 4. Pandemic COVID-19 sparked the most devastating crisis experienced by multi-sectors with prolonged problems and uncertainty. Since the beginning of the implementation of the Enforcement of Community Acvitity Restriction (ECAR) Level 4, there have been many polemics caused by the lack of policy socialization to all society levels, implementation transparency and social grants accountability. This study uses the consructivist paradigm in the form of qualitative descriptive with the formal evaluation approach. This Enforcement of Community Acvitity Restriction (ECAR) Level 4 is the only “Top Down” or centralized policy base, and less decentralized the decentralization and concurrent. The three stakeholders (government, public and private sector) need to improve the collaboration to achieve the synergy. The government needs to take actions to be more interactive, negotiable, open to dialogue and facilitating all stakeholders in order to help people in this difficult situation for getting the full support from all stakeholders.